Strategi Pemasaran UMKM Kerupuk dalam Meningkatkan Daya Saing dan Keberlanjutan Usaha: Studi Kasus di Tempat Usaha Kerupuk Poli Ibu Irsyat - Agustina Nur Qomariah; Sri Redjeki; Denok Mugi Hidayanti (Jurnal Riset Ekonomi dan Akuntansi, 2026)
This study aims to analyze the marketing strategies implemented by Mrs. Irsyat’s Poli Crackers MSME in Sukowono Village, assess their contribution to business competitiveness, and examine their role in supporting business sustainability. The study employed a qualitative approach with a case study method conducted in Sukowono Village, Sukowono District, Jember Regency. Research informants included the business owner, employees, consumers, and resellers selected through purposive sampling. Data were collected through in-depth interviews, observation, and documentation, then analyzed using the Miles and Huberman model consisting of data reduction, data presentation, and conclusion drawing. Data validity was ensured through source triangulation, technique triangulation, and member checking. The findings indicate that the MSME applies relatively simple marketing strategies adapted to local market conditions, including product quality improvement, competitive pricing, utilization of local distribution channels through small shops and resellers, and word-of-mouth promotion. These strategies have proven effective in increasing competitiveness, as reflected by higher sales, growing customer numbers, and the product’s distinctive taste advantage. Furthermore, the strategies contribute to business sustainability through sales stability, customer loyalty, and gradual business growth. Nevertheless, several challenges remain, including limited capital, labor shortages, and the underutilization of digital technology. Therefore, more innovative and technology-based marketing strategies are needed to support sustainable business development.